MELD Score Is Not Related to Spontaneous Bacterial Peritonitis - Luciana Haddad; Tatiana Morgado Conte; Liliana Ducatti; Lucas Nacif; Luiz Augusto Carneiro D’Albuquerque; Wellington Andraus (Gastroenterology Research and Practice)
This study investigates the correlation between SBP and repeated paracentesis, and its relation to MELD score, in cirrhotic patients with refractory ascites in an outpatient setting. Through the data base, 148 cirrhotic patients were prospectively included in the study with refractory ascites undergoing relief paracentesis from March 2012 to March 2013. Demographics data, etiology of liver disease, MELD score, and inscription on the waiting list for liver transplantation were analyzed. The ascites removed was analyzed through cellular count and culture for the diagnosis of spontaneous bacterial peritonitis. The cirrhotic patients underwent a total of 854 paracentesis procedures in the ambulatory setting during the study period. Eighty-one patients (54%) were on the waiting list for liver transplantation. Patients on the liver transplant list had higher associated costs due to a higher total number of outpatient paracentesis procedures (394.7 ± 512.3 versus 291.7 ± 384.7) and a higher volume drained per procedure (6.5 ± 8.5 versus 4.8 ± 6.4). There were 28 episodes of SBP (3.3%) diagnosed in 24 patients. In conclusion, the prevalence of asymptomatic SBP in cirrhotic patients with refractory ascites undergoing repeated paracentesis is low. MELD score is not related to spontaneous bacterial peritonitis.